The Impact of Infection Versus Colonization on Clostridioides difficile Environmental Contamination in Hospitalized Patients With Diarrhea. (9th February 2022) - Warren, Bobby G; Turner, Nicholas A; Addison, Rachel; Nelson, Alicia; Barrett, Aaron; Addison, Bechtler; Graves, Amanda; Smith, Becky; Lewis, Sarah S; Weber, David J; Sickbert-Bennett, Emily E; Anderson, Deverick J
Abstract: Background: Patients with Clostridioides difficile infections (CDIs) contaminate the healthcare environment; however, the relative contribution of contamination by colonized individuals is unknown. Current guidelines do not recommend the use of contact precautions for asymptomatic C difficile carriers. We evaluated C difficile environmental contamination in rooms housing adult inpatients with diarrhea based on C difficile status. Methods: We performed a prospective cohort study of inpatient adults with diarrhea who underwent testing for CDI via polymerase chain reaction (PCR) and enzyme immunoassay (EIA). Patients were stratified into cohorts based on test result: infected (PCR + /EIA + ), colonized (PCR + /EIA − ), or negative/control (PCR − ). Environmental microbiological samples were taken within 24 hours of C difficile testing and again for 2 successive days. Samples were obtained from the patient, bathroom, and care areas. Results: We enrolled 94 patients between November 2019 and June 2021. Clostridioides difficile was recovered in 93 (38%) patient rooms: 44 (62%) infected patient rooms, 35 (43%) colonized patient rooms ( P  = .08 vs infected 38 patient rooms), and 14 (15%) negative patient rooms ( P  < .01 vs infected; P  < .01 vs colonized). Clostridioides difficile was recovered in 40 (56%), 6 (9%), and 20 (28%) of bathrooms, care areas and patient areas in 40 infected patient rooms; 34 (41%), 1 (1%), and 4 (5%) samples in colonized patient rooms; and 12 (13%), 1 (1%), and 3 (3%) of samples in negative patient rooms, respectively. Conclusions: Patients colonized with C difficile frequently contaminated the hospital environment. Our data support the use of contact precautions when entering rooms of patients colonized with C difficile, especially when entering the bathroom. Abstract : Recovery of C difficile in colonized patient's rooms was similar to the recovery rate in rooms with actively infected patients in our study. Our data support the use of contact precautions when entering rooms of patients colonized with C difficile.